SENAM DISMENOREA TERHADAP PENURUNAN SKALA NYERI PADA REMAJA - Indah Dewi Sari; Nurrahmaton -; Novy Ramini Harahap; Umi Istiqomah (Universitas Prima Indonesia, 2023)
Introduction: The incidence of dysmenorrhea is quite high in the world. It is estimated that as many as 90% of women in Indonesia have experienced dysmenorrhea but do not report it to health services. Pain management can be done by a health worker using non-pharmacological methods such as dysmenorrhea exercises. Objective: This study aimed to determine the effect of dysmenorrhea exercise on reducing pain scale in female students at Darul Huffadh Islamic Boarding School Padang Lawas Utara. Method: This is quasi-experimental research with two groups pretest and posttest design. The research sample consisted of 20 respondents who experienced menstrual pain at the School. The sampling technique used purposive sampling. The sample was divided into 2 groups, namely the control group and the treatment group. Dysmenorrhea exercise was given 3 days for 30 minutes. Analysis used Wilcoxon Test analysis. The Result: That in the control group (without treatment) there was no effect on the intensity of menstrual pain with a sig value of 1,000. In the treatment group, giving dysmenorrhea exercise obtained an average of 5.50 and after being tested, it was found that doing dysmenorrhea exercises had an effect on decreasing the menstrual pain scale in young women. Conclusion: That dysmenorrhea exercise has an effect on reducing menstrual pain scale in young women. It is suggested that the health unit of Darul Huffadh Islamic Boarding School Padang Lawas Utara be able to provide dysmenorrhea exercises for female students who experience menstrual pain and to reduce..